2012
DOI: 10.1186/1471-2458-12-14
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional survey of prevalence and correlates of suicidal ideation and suicide attempts among prisoners in New South Wales, Australia

Abstract: BackgroundWe aimed to estimate the prevalence of suicidal ideation and suicide attempt among prisoners in New South Wales, Australia; and, among prisoners reporting suicidal ideation, to identify factors associated with suicide attempt.MethodsA cross-sectional design was used. Participants were a random, stratified sample of 996 inmates who completed a telephone survey. The estimated population prevalence of suicidal ideation and suicide attempt were calculated and differences by sex and Aboriginality were tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
121
5
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(144 citation statements)
references
References 31 publications
14
121
5
4
Order By: Relevance
“…Two-fifths (21%) of inmates had seriously thought about suicide; one in 10 had ever made a suicide attempt. Rates are lower than those reported in studies of prisoners in England and Wales (Singleton et al, 1998) and Australia (Larney, Topp, Indig, O'Driscoll, & Greenberg, 2012). Suicidal ideation and attempts are robust risk factors for suicide (Hayes, 1995) and must be taken seriously.…”
Section: Discussionmentioning
confidence: 66%
“…Two-fifths (21%) of inmates had seriously thought about suicide; one in 10 had ever made a suicide attempt. Rates are lower than those reported in studies of prisoners in England and Wales (Singleton et al, 1998) and Australia (Larney, Topp, Indig, O'Driscoll, & Greenberg, 2012). Suicidal ideation and attempts are robust risk factors for suicide (Hayes, 1995) and must be taken seriously.…”
Section: Discussionmentioning
confidence: 66%
“…We found three studies of risk factors for suicide in European prison populations, in which associations were reported with violent offences, 20 increased cell occupancy, 21 and self-harm 22 . Furthermore, we identified one cross-sectional study of self-harm in prison that investigated correlates of lifetime suicidal ideation 23 . Rates of suicide 3,20 and lifetime rates of self-harm 19 are consistently higher in custody than in the general population, and self-harm is a major risk factor for suicide in prisoners 6,22 .…”
Section: Tablementioning
confidence: 99%
“…A meta-analysis of nearly 5000 suicide deaths in prisons (mostly in the US) found that the risk of suicide was 15 times higher among those who experienced recent suicidal ideation, and approximately 50% of people who died by suicide in prison had a history of self-harm (Fazel et al 2008). In an Australian study, 15–21% and 34–44% of people in prison reported a lifetime history of attempted suicide and suicidal ideation, respectively (Larney et al 2012). …”
Section: Introductionmentioning
confidence: 99%